Strategi Humas Pondok Pesantren Al-Qodiri Dalam Mempertahankan Citra Pesantren - Agus Ainul Yaqin M.S; Reza Fahlifi (Medio Jurnal Ilmu Komunikasi, 2023)
The focus of this research is how is the PR strategy in maintaining the image of Islamic boarding schools. This study aims to determine the strategies used by the public relations of the Al-Qodiri 1 Jember Islamic boarding school in maintaining its image. This study uses a descriptive qualitative approach, with data collected from observations, interviews and documentation. The data that has been collected is then analyzed and described and conclusions drawn. There are several strategies found by researchers in maintaining the image of Islamic boarding schools and are the results of this research, including: Strategy through alumni, making events such as dzikir manaqib events, putting up banners, working with PT. Seaven Dream Group, adding learning facilities, makes students able to compete at the national and international levels and also uploads Islamic boarding school achievements.